Collective Action and Property Rights (CAPRi) - International Food Policy Research Institute (International Food Policy Research Institute, 1995)
This site contains analysis and practices on the ways that collective action and property rights institutions influence the efficiency, equity, and sustainability of natural resource use and reduce poverty.